A comparison of clinical outcomes following kyphoplasty for osteoporotic compression fractures of the thoracic and lumbar spine: a systematic review and meta-analysis - Kann, Michael R.; Ramanathan, Rahul; Gonzalez, Christopher; Edwards, Timothy; Cisneros, Christian; Como, Christopher J.; Zou, Trudy; Lutes, Sarah; Chagas, Julia; Spitnale, Michael J.; Wawrose, Richard A.; Lee, Joon Y.; et al. (Frontiers in Musculoskeletal Disorders, 2025)
IntroductionKyphoplasty is a minimally invasive treatment for osteoporotic vertebral compression fractures (VCFs) aimed at restoring vertebral height and alleviating pain. However, despite its widespread use, kyphoplasty outcomes are typically analyzed without distinguishing between thoracic and lumbar regions. Given the anatomical and biomechanical differences between these regions, it is crucial to compare the efficacy and complication rates of kyphoplasty based on spinal location. This review seeks to evaluate these distinctions and explore their potential clinical implications to inform patient expectations and procedural understanding.MethodsA comprehensive search strategy was developed using concepts of kyphoplasty, compression fractures, and spinal regions. Resulting literature underwent title, abstract, and full-text screening using the inclusion criteria: (1) Patients underwent kyphoplasty for osteoporotic VCFs of the thoracic and lumbar spine, (2) Clinical, perioperative, or postoperative outcome measures were available, and (3) Outcome measures were subcategorized into thoracic or lumbar spinal regions. Meta-analysis was performed using a random effects model. The ROBINS-I tool was used to evaluate bias.ResultsTwenty-five manuscripts were included in final analysis. Meta-analysis revealed operative time and injected cement volume were 43.07 minutes [95% CI (35.34, 50.79)] and 4.61 ml [95% CI (3.79, 5.43)] in the lumbar spine and 56.42 min [95% CI (41.03, 71.81)] and 4.25 ml [95% CI (3.56, 4.93)] in the thoracic spine, respectively. Likewise, the incidence of cement leakage and subsequent adjacent level fractures were 13% [95% CI (7%, 22%)] and 5% [95% CI (2%, 12%)] in the lumbar spine and 19% [95% CI (10%, 32%)] and 10% [95% CI (2%, 33%)] in the thoracic spine, respectively. Lastly, the post-operative decrease in visual analog scale pain was 5.59 [95% CI (5.23, 5.94)] in the lumbar spine and 5.49 [95% CI (4.79, 6.19)] in the thoracic spine. Across studies, the primary risk of bias was due to confounding variables, resulting in a serious risk of bias in 12 studies (48.0%).DiscussionKyphoplasty provides comparable outcomes in thoracic and lumbar VCFs, with no clinically significant differences in pain relief or procedural effectiveness. Despite anatomical differences, the procedure remains safe and effective in both regions, warranting further research on spinal region-specific outcomes.